In Vitro and In Vivo Potential of RH Strain of Toxoplasma Gondii (Type Ι) in Tissue Cyst Forming - Qasem AsgariI; Hossein Keshavarz; Saeedeh Shojaee; Mohammad Hossein Motazedian; Mehdi Mohebali; Ramin MIRI; Davood Mehrabani; Mostafa Rezaeian (Iranian Journal of Parasitology, 2013)
Background: Based on recent studies, there are controversial reports on the capacity of tissue cyst forming of Toxoplasma gondii RH strain. In this study, the capacity was evaluated by in vivo and in vitro experiments.Methods: RH strain was subcutaneously inoculated to ten Wistar rats. After one month, their blood, brain, tongue and diaphragm were collected and evaluated by MAT, PCR, pathological and bioassay methods. The parasite was cultivated in the cell monolayer. To change to bradyzoite, the media pH was altered to 6.8. Biological aspect of the bradyzoites was evaluated by incubation in acidic pepsin and it's inoculation in ten BALB/c mice.Results: All rats showed antibodies to Toxoplasma at titers ≥1:320 but no DNA and tissue cyst were detected in the tissues. Following intraperitoneal inoculation of rats’ brain homogenate into BALB/c mice, no infection was established in none of the animals. During presence of cell culture, in acid media for a 3-5 days period, cyst-like structures were noticed when they were stained with PAS. The visible bradyzoites in the cysts that were incubated in acid pepsin medium were not able to kill any mice.Conclusion: This study confirmed that Iranian RH strain has lost the potential of tissue cyst forming in rats and bradyzoites cultivated in cell culture lost their resistance to acidic condition, so this strain can be a candidate for future vaccine researches.